Unusual Presentation of Leiomyoma in the Hindfoot - Abdullah Zaher; Jaouad Yasser; Daniel Badaro; Noureddine Sekkach (Case Reports in Orthopedics)
A leiomyoma is a benign smooth muscle tumor that is most commonly found in the uterus. Limited studies have reported leiomyoma of the foot, rendering it an usual finding. We present a case of a 57-year-old female patient who presented to the clinic for a painless mass on the posteromedial side of the right heel. It was diagnosed by the radiologist on MRI as a probable schwannoma. The patient underwent surgical excision of this mass which turned out to be a leiomyoma on pathology report. Although foot leiomyoma is a rare finding, leiomyoma should be listed in the differential diagnosis when evaluating foot soft tissue masses. It is difficult to confirm the diagnosis clinically and radiographically, yet a histologic evaluation can affirm the diagnosis. Surgical excision is the treatment of choice offering immediate symptomatic relief.